2004
DOI: 10.1007/s00216-004-2501-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace amounts of phosphate by flow-injection photometry

Abstract: This paper describes a simple and rapid procedure for determination of traces of phosphate by means of molybdenum blue chemistry. The use of a cost-effective home-made flow cell with a long path length in combination with a light emitting diode (LED) and a photodiode (PD) is demonstrated as a simple absorbance detector for flow-injection analysis. In this method, a sample is injected into the carrier stream through an injection valve and mixed online with mixed reagent (a mixture of molybdate, bismuth, and asc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The peak intensity at the GRC electrode was several-times larger than that at the platinum electrode. The first reason for this experimental fact is a difference between the adsorption behaviors of 12 5-. It has been reported that GRC is a functional material that can strongly adsorb many kinds of materials.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak intensity at the GRC electrode was several-times larger than that at the platinum electrode. The first reason for this experimental fact is a difference between the adsorption behaviors of 12 5-. It has been reported that GRC is a functional material that can strongly adsorb many kinds of materials.…”
Section: Reagentsmentioning
confidence: 99%
“…[9][10][11][12] In recent years, many methods for the determination of phosphate ion have been developed. Among them, spectrophotometry based on a chemical reduction of molybdophosphate ion (the molybdenum-blue method) is a representative, and its various versions have been proposed in compliance with many analytical requests.…”
Section: Introductionmentioning
confidence: 99%
“…DRP is an operational definition for soluble phosphate which passes a 0.45 µm filter and can be measured colorimetrically [5] [6]. However, some inorganic condensed phosphorus (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Small size, low cost, high stability of the radiation beam, and long lifetime are the main features of LEDs which explains its widespread use in different analytical procedures. [7][8][9] The availability of LEDs with wavelengths ranging from ultraviolet (l ca. 380 nm) to near infrared (l ca.…”
Section: Introductionmentioning
confidence: 99%
“…2,17 There are a few studies on the use of LEDs as photodetectors. 8,19 The measurement was done using the LED capacitance effect, which presents a relationship da SIlva et al…”
Section: Introductionmentioning
confidence: 99%